(untitled) (The Journal of Psychology and Sociology, 2020)
The article socio-economic changes in modern society have a significant impact on the formation of the personality of the future generation and the level of their socio-psychological adaptation. This oc-curs in adolescence, characterized by contraindications. Adolescence includes such complex changes as the formation of self-awareness and behavior, self-esteem and the development of an independent, independent system of self-esteem and self-esteem. Such conditions provided the basis for a broad dis-cussion of evaluation at this stage of development. At the same time, along with various psychological and social factors, self-esteem contributes to the normal implementation of the socialization of the child and the norms of social behavior. The article reveals the essence of the concept of” self-esteem “ of psychological characteristics of a modern teenager in the personal development of a modern teenager, forms a structural model of self-esteem on the basis of these theoretical knowledge and defines the characteristics of self-esteem of adolescents in modern conditions of training and education. On its basis, the features of self-assessment of students in grades 7-10. It is also important to apply this scientific work to improve the interaction and understanding of adolescents in the family and to train teachers working with adolescents. Key words: adolescence, self-knowledge, self-esteem, image I”, autonomy of behavior, relation-ships with peers.